2015
DOI: 10.1089/hum.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficacy from Gene Therapy in Pompe Disease Using Coreceptor Blockade

Abstract: Enzyme replacement therapy (ERT) is the standard-of-care treatment of Pompe disease, a lysosomal storage disorder caused by deficiency of acid a-glucosidase (GAA). One limitation of ERT with recombinant human (rh) GAA is antibody formation against GAA. Similarly, in adeno-associated virus (AAV) vector-mediated gene transfer for Pompe disease, development of antibodies against the GAA transgene product and the AAV vector prevents therapeutic efficacy and vector readministration, respectively. Here a nondepletin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…The formation of HSAT blocked the uptake of GAA and provoked fatal hypersensitivity reactions in GAA-KO mice with Pompe disease. 20 Although Nayak and colleagues demonstrated that immune reactions were mediated by a helper T cell type 2 response associated with high-titer IgG1 during ERT, 24 we observed alterations in many subclasses of immunoglobulins, implying a more complex response to AAV vector-mediated GAA expression in GAA-KO mice, 8 Therefore, we have developed coreceptor blockade to eliminate CD4 + T lymphocyte help, and combined this immune tolerance induction with b 2 -agonists to enhance CI-MPRmediated uptake of GAA during gene therapy in Pompe disease. Comparison of biochemical correction after immune tolerance induction with anti-CD4 mAb or liver-specific expression of GAA.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The formation of HSAT blocked the uptake of GAA and provoked fatal hypersensitivity reactions in GAA-KO mice with Pompe disease. 20 Although Nayak and colleagues demonstrated that immune reactions were mediated by a helper T cell type 2 response associated with high-titer IgG1 during ERT, 24 we observed alterations in many subclasses of immunoglobulins, implying a more complex response to AAV vector-mediated GAA expression in GAA-KO mice, 8 Therefore, we have developed coreceptor blockade to eliminate CD4 + T lymphocyte help, and combined this immune tolerance induction with b 2 -agonists to enhance CI-MPRmediated uptake of GAA during gene therapy in Pompe disease. Comparison of biochemical correction after immune tolerance induction with anti-CD4 mAb or liver-specific expression of GAA.…”
Section: Discussionmentioning
confidence: 73%
“…Induction of immune tolerance was achieved by two different approaches: one approach was focused on the suppression of immune responses through liver-specific expression of GAA 25 and the second acted through blockade of helper T lymphocyte activation with anti-CD4 mAb. 8 At present the need for the induction of immune tolerance is greatest for patients with infantile-onset Pompe disease. In the meantime, the need to induce CI-MPR expression for improvement of GAA uptake in skeletal muscle is greatest for patients with lateonset Pompe disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations